Testing the validity and reliability of the Depression Anxiety Stress Scale (DASS)-21 instrument for individuals with psychodermatology - Nada, Qothrun; Herdiana, Ike; Andriani, Fitri (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
Individual psychological health can be seen from the health of the skin. Some skin diseases such as psoriasis and atopic dermatitis can be exacerbated by psychological problems. Based on this, a collaboration between specialist doctors and psychologists is needed to screen for psychological disorders in sufferers. One psychological screening instrument is the Depression Anxiety Stress Scale (DASS)-21; this study aims to test its validity and reliability. Non-probability convenience sampling was employed, and 292 participants aged 18-54 were willing to take part in the study. An internal structure validity test was conducted using confirmatory factor analysis, while concurrent validity was assessed by correlating DASS-21 with PHQ-9, GAD-7 and PSS scores. The reliability test was analyzed using composite reliability. The results of the CFA analysis showed that the data matched Lovibond's theory and that all DASS-21 items were valid (RMSEA =.076, CFI=.961, TLI = .955, SRMR = .065). The results of the concurrent analysis showed that the three scales had a positive correlation with the dimensions of DASS-21, while the reliability results showed a satisfactory value (.850 – .923). The results of the study indicate that DASS-21 is a valid and reliable instrument and can be used to measure depression, anxiety and stress in individuals with psoriasis and atopic dermatitis.